Meta-analysis on prevalence of vaginal group B streptococcus colonization and preterm births in India. (3rd August 2022) - Ashary, Nancy; Singh, Abhishek; Chhabria, Karisma; Modi, Deepak
Abstract: Objective: Preterm birth is a major cause of neonatal morbidity and mortality. Vaginal colonization of Group B Streptococci (GBS) is associated with increased risk of preterm birth. However, the association of GBS colonization and preterm births in the Indian context remains an unrecognized problem. Data sources: Data was collected using various online search tools from 36 (1981–2019) Indian studies comprising 9778 cases. Method of study selection: Studies reporting the prevalence of GBS colonization in the Indian population were included. Tabulation, Integration, and Results: The prevalence of GBS colonization in pregnant Indian women was estimated to be 7.8% (763/9778) with wide heterogeneity across studies. The prevalence of GBS was 7.4% when culture methods were used and 11.6% with use of immunological methods. The detection rate of GBS almost doubled when enrichment was used in the culture method (8.1 vs. 5%). The risk of preterm delivery was higher (OR 7.9) among women with GBS colonization as compared to those without GBS. Conclusions: As compared to the western population, there is low prevalence of GBS colonization among Indian pregnant women; however, the risk of preterm births with GBS colonization is higher. There is a need to implement a universal GBS screening program prior to intrapartum antibiotic prophylaxis in women experiencing preterm births.